Pengaruh Komitmen Kerja Kualitas SDM dan Lingkungan Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Arjasa Kabupaten Sumenep - Mohammad Hariyanto; Abdul Kodir Djaelani; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine 1) Effect of work commitment, quality of human resources, work environment on employee performance, 2) Effect of work commitment on employee performance, 3) Effect of quality of human resources on employee performance. employee performance, 4) The influence of the work environment on employee performance.This study uses quantitative methods with descriptive and inferential analysis. The number of samples used were 36 employee respondents at the Arjasa District Office, Sumenep Regency. Sources of data used are primary and secondary sources. Collecting data using a questionnaire with Likert scale measurements while the analysis used is instrument test, normality test, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R2) with SPSS 16.0 tools. The results of this study indicate that 1), work commitment has an influence on employee performance, 2), quality of human resources has an influence on employee performance, 3), work environment has an influence on employee performance. Keywords : Work Commitment, Quality of Human Resources, Work Environment and Employee Performance.